Epidemiologic Features of Vulvovaginal Candidiasis among Reproductive-Age Women in India - Sujit D. Rathod; Jeffrey D. Klausner; Karl Krupp; Arthur L. Reingold; Purnima Madhivanan (Hindawi Limited, 2012)
Background. Vulvovaginal candidiasis is characterized by curd-like vaginal discharge and itching, and is associated with considerable health and economic costs. Materials and Methods. We examined the incidence, prevalence, and risk factors for vulvovaginal candidiasis among a cohort of 898 women in south India. Participants completed three study visits over six months, comprised of a structured interview and a pelvic examination. Results. The positive predictive values for diagnosis of vulvovaginal candidiasis using individual signs or symptoms were low (<19%). We did not find strong evidence for associations between sociodemographic characteristics and the prevalence of vulvovaginal candidiasis. Women clinically diagnosed with bacterial vaginosis had a higher prevalence of vulvovaginal candidiasis (Prevalence 12%, 95% CI 8.2, 15.8) compared to women assessed to be negative for bacterial vaginosis (Prevalence 6.5%, 95% 5.3, 7.6); however, differences in the prevalence of vulvovaginal candidiasis were not observed by the presence or absence of laboratory-confirmed bacterial vaginosis. Conclusions. For correct diagnosis of vulvovaginal candidiasis, laboratory confirmation of infection with Candida is necessary as well as assessment of whether the discharge has been caused by bacterial vaginosis. Studies are needed of women infected with Candida yeast species to determine the risk factors for yeast's overgrowth.